2020
DOI: 10.1097/aog.0000000000004128
|View full text |Cite
|
Sign up to set email alerts
|

High Concentrations of Nitric Oxide Inhalation Therapy in Pregnant Patients With Severe Coronavirus Disease 2019 (COVID-19)

Abstract: High-dose nitric oxide is a novel treatment associated with improved oxygenation and decreased tachypnea in pregnant patients with severe coronavirus disease 2019 (COVID-19).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 15 publications
(16 reference statements)
1
41
0
4
Order By: Relevance
“…Five of six patients had two negative test results by nasopharyngeal swab for SARS-CoV-2 within 28 days from admission. The result of the study showed that 160–200 ppm iNO appeared to be well tolerated, and might benefit pregnant patients with hypoxic respiratory failure ( Table 1 ) [ 97 ].…”
Section: Application Of No In Clinical Treatmentmentioning
confidence: 99%
“…Five of six patients had two negative test results by nasopharyngeal swab for SARS-CoV-2 within 28 days from admission. The result of the study showed that 160–200 ppm iNO appeared to be well tolerated, and might benefit pregnant patients with hypoxic respiratory failure ( Table 1 ) [ 97 ].…”
Section: Application Of No In Clinical Treatmentmentioning
confidence: 99%
“…High-dose inhaled nitric oxide (160-200 ppm) has demonstrated antimicrobial effects against bacteria and viruses (including SARS-CoV), and is used as an adjunct treatment for acute respiratory distress syndrome and pulmonary hypertension. A case series of pregnant patients with severe COVID-19 treated with high-dose nitric oxide demonstrated improvement in hypoxemia and tachypnea with no adverse neonatal effects 72 .…”
Section: Experimental Drugs For Covid-19 In the Setting Of Clinical Tmentioning
confidence: 98%
“…Ongoing clinical trials use higher doses of iNO at 80 ppm and even short periods of 200 ppm in a small group of pregnant patients infected with COVID-19 without reported side effects. 5 In addition, we do not know at which point in time the pharmacodynamic effect of iNO would be most beneficial.…”
Section: E D I T O R I a Lmentioning
confidence: 99%